2021
DOI: 10.1111/ina.12788
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls in indoor dust from urban dwellings of Lahore, Pakistan: Congener profile, toxicity equivalency, and human health implications

Abstract: This study is the pioneer assessment of the PCBs in indoor dust particles (from air conditioners) of an urbanized megacity from South Asian. The ∑35 PCB concentration ranged from 0.27 to 152.9 ng/g (mean: 24.84 ± 22.10 ng/g). The tri‐ and tetra‐PCBs were dominant homologues, contributing 57.36% of the total PCB concentrations. The mean levels of Σ8‐dioxin‐like (DL), Σ6‐indicator PCBs and WHO2005‐TEQ for DL‐PCBs were 2.22 ± 2.55 ng/g, 9.49 ± 8.04 ng/g and 4.77 ± 4.89 pg/g, respectively. The multiple linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Another study highlighted the adverse PCB contamination in this site especially near industrial and waste dumping areas (Syed et al, 2014). A study conducted on indoor environment of district Lahore also reported high levels of PCBs as compared to other parts of the country (Aslam et al, 2021). It was followed by Multan and Faisalabad with 17.45% and 16.86% contributions.…”
Section: Spatial Dispersal Patterns and Sources Of Pcbs In Bovine Milkmentioning
confidence: 76%
“…Another study highlighted the adverse PCB contamination in this site especially near industrial and waste dumping areas (Syed et al, 2014). A study conducted on indoor environment of district Lahore also reported high levels of PCBs as compared to other parts of the country (Aslam et al, 2021). It was followed by Multan and Faisalabad with 17.45% and 16.86% contributions.…”
Section: Spatial Dispersal Patterns and Sources Of Pcbs In Bovine Milkmentioning
confidence: 76%
“…Tariq et al [160] reported that PM 2.5 , formaldehyde, and CO were responsible for chronic respiratory diseases such as breath shortening, bronchitis, and asthma in Karachi. Aslam et al [161] scrutinized the effects of indoor polychlorinated biphenyls on human health in the Pakistani population. The pollutants were inhaled or ingested through the indoor air.…”
Section: Major Health Hazards Of Indoor Air Contaminationmentioning
confidence: 99%
“…Similarly, the air in houses with backyard e-waste recycling has two to three times the PCB contamination than indoor air in urban areas [ 87 ]. Therefore, all sources of airborne PCBs should be considered when assessing PCB concentrations in indoor air [ 86 ].…”
Section: Occurrence Of Pcbs In the Airmentioning
confidence: 99%
“…PCBs pose a health risk to humans through three routes of exposure (oral ingestion, inhalation, and dermal absorption). While dietary consumption represents a major route of exposure in adults, inhalation presents a two times higher carcinogenic risk, especially among children [ 86 ]. In 2015, PCBs were classified as a Group 1 carcinogen (carcinogenic to humans) by the International Agency for Research on Cancer, which further highlights the significance of their oncogenic effects, and makes them a major toxicological concern across the globe [ 95 ].…”
Section: Health Impactmentioning
confidence: 99%